The host galaxy of GRB 980425/SN1998bw: a collisional ring galaxy. Issue 4 (14th March 2019) - Arabsalmani, M; Roychowdhury, S; Starkenburg, T K; Christensen, L; Le Floc'h, E; Kanekar, N; Bournaud, F; Zwaan, M A; Fynbo, J P U; Møller, P; Pian, E
ABSTRACT: We report Giant Metrewave Radio Telescope (GMRT), Very Large Telescope (VLT), and Spitzer Space Telescope observations of ESO 184−G82, the host galaxy of GRB 980425/SN 1998bw, that yield evidence of a companion dwarf galaxy at a projected distance of 13 kpc. The companion, hereafter GALJ193510-524947, is a gas-rich, star-forming galaxy with a star formation rate of $\rm 0.004\, M_{\odot }\, yr^{-1}$, a gas mass of $10^{7.1± 0.1} \, M_{\odot}$, and a stellar mass of $10^{7.0± 0.3} \, M_{\odot}$ . The interaction between ESO 184−G82 and GALJ193510-524947 is evident from the extended gaseous structure between the two galaxies in the GMRT H i 21 cm map. We find a ring of high column density H i gas, passing through the actively star-forming regions of ESO 184−G82 and the GRB location. This ring lends support to the picture in which ESO 184−G82 is interacting with GALJ193510-524947. The massive stars in GALJ193510-524947 have similar ages to those in star-forming regions in ESO 184−G82, also suggesting that the interaction may have triggered star formation in both galaxies. The gas and star formation properties of ESO 184−G82 favour a head-on collision with GALJ193510-524947 rather than a classical tidal interaction. We perform state-of-the-art simulations of dwarf–dwarf mergers and confirm that the observed properties of ESO 184−G82 can be reproduced by collision with a small companion galaxy. This is a very clear case of interaction in a gamma-ray burst host galaxy and of interaction-driven star formation giving rise to a gamma-ray burst in a dense environment.